(untitled) (Journal of Scientific Research, 2016)
The present study investigated the water quality of Shitalakhya River, phytoplankton abundance, diversity and the effect of pollutants on phytoplankton as well as the primary productivity. The water of the collected samples was mostly alkaline (7.01-8.2) and showed a wide range of variation in EC (1171-2700 ?S/cm), TDS (576-1345 mg/L), DO (0.92-2.7 mg/L), free-CO2 (15-31 mg/L), BOD (12.03-28.38 mg/L) and COD (101.2-109.2 mg/L). A total of 62 species were identified of which 9 belonged to Chlorophyceae, 11 Cyanophyceae, 14 Euglenophyceae and 28 Bacillariophyceae. Among all the members, Bacillariophyceae were found to be dominant and lowest of Chlorophyceae indicates that this group is more sensitive to the pollutants discharged by the industry.